Phat – Persistent Homology Algorithms Toolbox - Bauer, Ulrich; Kerber, Michael; Reininghaus, Jan; Wagner, Hubert (Journal of symbolic computation, 2017)
Phat is an open-source C++ library for the computation of persistent homology by matrix reduction, targeted towards developers of software for topological data analysis. We aim for a simple generic design that decouples algorithms from data structures without sacrificing efficiency or user-friendliness. We provide numerous different reduction strategies as well as data types to store and manipulate the boundary matrix. We compare the different combinations through extensive experimental evaluation and identify optimization techniques that work well in practical situations. We also compare our software with various other publicly available libraries for persistent homology.